Do COVID-19 CT features vary between patients from within and outside mainland China? Findings from a meta-analysis - Hou, Nianzong; Wang, Lin; Li, Mingzhe; Xie, Bing; He, Lu; Guo, Mingyu; Liu, Shuo; Wang, Meiyu; Zhang, Rumin; Wang, Kai (Frontiers in Public Health, 2022)
Abstract Background: Chest CT plays an important role in detecting patients suspected COVID-19, however, there are no systematic summaries about whether the chest CT findings in China's Mainland are applicable to outside. Method: Relevant studies were retrieved comprehensively by searching PubMed, Embase and Cochrane Library before April 15, 2022. QUADAS was used to evaluate the qualities of the studies included, which were divided into two groups according to patients in or outside China's Mainland. The data of diagnostic performance, unilateral or bilateral lung involvement and typical imaging appearances of chest CT were extracted, and then, meta-analyses were performed by R software to compare the CT features of COVID-19 pneumonia between patients in and outside China's Mainland. Results: Of 8258 studies screened, 19 studies with 3400 patients in China's Mainland and 14 studies with 554 outside were included. There was generally low risk for quality assessment and publication bias. The diagnostic value of Chest CT between patients in and outside China's Mainland are similar(93%,91%). The pooled incidence of unilateral lung involvement (15%,7%), crazy paving sign (31%,21%), mixed GGO and consolidation (51%,35%), air-bronchogram (44%,25%), vascular engorgement (59%,33%), bronchial wall thicking (19%,12%) and septal thicking (39%,26%) in patients inside China's Mainland were significantly higher than those outside, however, the incidence rates of bilateral lung involvement (75%,84%), GGO (78%,87%), consolidations (45%,58%), nodules (12%,17%) and pleural effusion (9%,15%) were significantly less. Conclusion: Considering that the chest CT features of patients in China's Mainland couldn’t mirror those outside, radiologists and clinicians should be familiar with the various suggestive CT presentations of COVID-19 in different regions.